Cloning and purification of the first termicin-like peptide from the cockroach Eupolyphaga sinensis. Issue 1 (December 2016) - Liu, Zichao; Yuan, Kehua; Zhang, Ruopeng; Ren, Xuchen; Liu, Xiaolong; Zhao, Shuhua; Wang, Dingkang
Abstract Background Termicin is an antimicrobial peptide with six cysteines forming three disulfide bridges that was firstly isolated from the salivary glands and hemocytes of the termitePseudacanthotermes spiniger . In contrast to many broad-spectrum antimicrobial peptides, termicin is most active against filamentous fungi. Although more than one hundred complementary DNAs (cDNAs) encoding termicin-like peptides have been reported to date, all these termicin-like peptides were obtained from Isoptera insects. Methods The cDNA was cloned by combination of cDNA library construction kit and DNA sequencing. The polypeptide was purified by gel filtration and reversed-phase high performance liquid chromatography (RP-HPLC). Its amino acid sequence was determined by Edman degradation and mass spectrometry. Antimicrobial activity was tested against several bacterial and fungal strains. The minimum inhibitory concentration (MIC) was determined by microdilution tests. Results A novel termicin-like peptide with primary structure ACDFQQCWVTCQRQYSINFISARCNGDSCVCTFRT was purified from extracts of the cockroachEupolyphaga sinensis (Insecta: Blattodea). The cDNA encoding Es-termicin was cloned by cDNA library screening. This cDNA encoded a 60 amino acid precursor which included a 25 amino acid signal peptide. Amino acid sequence deduced from the cDNA matched well with the result of protein Edman degradation. Susceptibility test indicated that Es-termicin showed strong ability to kill fungi with a MIC of 25 μg/mL againstCandida albicans ATCC 90028. It only showed limited potency to affect the growth of Gram-positive bacteria with a MIC of 200 μg/mL againstEnterococcus faecalis ATCC 29212. It was inactive against gram-negative bacteria at the highest concentration tested (400 μg/mL). Es-termicin showed high sequence similarity with termicins from many species of termites (Insecta: Isoptera). Conclusions This is the first report of a termicin-like peptide isolated fromE. sinensis that belongs to the insect order Blattodea. Our results demonstrate the diversity of termicin-like peptides, as well as antimicrobial peptides in insects.